Screening and detection of delirium in an adult critical care setting: a best practice implementation project. Issue 4 (5th December 2021) - de Souza-Talarico, Juliana N.; da Silva, Fernanda C.; de Motta Maia, Flávia O.; Sichieri, Karina; Cardoso, Diley; Garcia, Paulo; Matos, Tatiane M.; Nascimento, Tatiane S.
ABSTRACT: Aim: To assess compliance with evidence-based practice regarding screening and detection of delirium in adult patients at the ICU from a university hospital. Methods: The compliance rates were evaluated using the Joanna Briggs Institute Practical Application of Clinical Evidence System and Getting Research into Practice audit and feedback tool. This strategy was designed in three phases: (1) establishing a team and conducting a baseline audit based on criteria informed by the evidence; (2) reflecting on the results of the baseline audit and designing and implementing strategies to address noncompliance found in the baseline audit informed by the JBI Getting Research into Practice framework; and (3) conducting a follow-up audit to assess the outcomes of the interventions implemented to improve practice and identify future practice issues to be addressed in subsequent audits. The implementation protocol was designed based on the primary barriers and facilitators identified in the baseline audit, allied to a training program and electronic medical records changes. Nursing documentation available in medical records from patients admitted in the ICU was used to assess the baseline and follow-up audit compliance rates. Results: None of the medical records evaluated before the implementation protocol showed compliance with the following audit criteria: a valid and reliable instrument is accessible in the ward environment (0%), the nursing care documentation supports that the Confusion Assessment Method for the Intensive Care Unit instrument is being used (0%) and population assessed for delirium includes all adults over the age of 65, cognitive impairment, dementia, or both, current hip fracture and severe illness (0%). After the evidence-based practice implementation, the follow-up audit revealed up to 100% compliance rates with those criteria, showing that all patients under risk were screened and assessed for delirium. The only exception was the Confusion Assessment Method for the Intensive Care Unit use, whose compliance was observed in 80.95% of the medical records. Conclusion: These findings support that baseline and follow-up audits allied to a delirium training program, and changes in the electronic nursing records increase the compliance rates related to the evidence-based practice for screening patients under risk and assessing delirium.